CORPORATE SOCIAL RESPONSIBILITY: Kajian Ekonomi, Sosial dan Lingkungan - Sufyati HS (Jurnal Sosiologi Reflektif, 2017)
The objective of this research is to evaluate the implementation of CSR program in Islamic banking with economic, social and environmental approach. The research method used is interview and spread the questionnaire to the respondent of CSR beneficiaries, supported by empirical data and literature approach. The analytical technique uses the analysis of Simple Linear Regression. The findings of the research by using t-test that economic aspect, more significant from social and environmental aspect. Economic field run by Islamic bank that is by giving loan without margin or loan of virtue, by organizing poor society in small groups consist of five people, through business assistance and entrepreneurship training to establish business independence. In this case, Islamic banks cooperate with social institutions, Baital-Mal wat Tamwil and Isalmic Financial Services Cooperative. Loan facility funds are obtained from fines, non-halal income, zakat, infaq, alms, and endowments of employees, customers, communities and other social funds. In the theoretical order, this study concurs with the theory of Elkington (1999) and Jim Ife (1995) that in community empowerment should be accompanied by a balanced, economic, social and environmental transformation, the power of that factor will shape the community's independence, in addition to other factors. Normatively, the implementation of CSR programs, driven by awareness to be socially responsible, but generally the interest to form corporate image through assistance feels more prominent, so have not thought about aspects of sustainability of development.Penelitian ini bertujuan  untuk mengevaluasi  implementasi  program CSR pada perbankan syariah dengan pendekatan ekonomi, sosial dan lingkungan. Metode penelitian yang digunakan yaitu  wawancara dan menyebarkan kuisioner kepada responden penerima manfaat CSR, didukung data empiris dan pendekatan literature.Tehnik analisis menggunakan analisis Simple Linear Regression. Temuan hasil penelitian dengan menggunakan t-test bahwa aspek ekonomi, lebih signifikan dari aspek sosial dan lingkungan. Bidang ekonomi yang dijalankan oleh bank syariah yaitu memberikan pinjaman tanpa margin atau pinjaman kebajikan, dengan mengorganisir masyarakat miskin dalam kelompok-kelompok kecil terdiri atas lima orang, melalui pendampingan usaha dan pelatihan kewirausahaan untuk membentuk kemandirian usaha. Dalam hal ini bank syariah bekerjasama dengan Lembaga sosial masyarakat, Baital-Mal wat Tamwil dan Koperasi Jasa Keuangan Syariah. Dana fasilitas pinjaman diperoleh dari denda, pendapatan non halal, zakat, infaq, sedekah dan wakaf  karyawan, nasabah, masyarakat, dan dana sosial lainnya. Dalam tatanan teoritis penelitian ini sependapat dengan teori Elkington (1999) dan Jim Ife (1995) bahwa dalam pemberdayaan masyarakat hendaklah disertai transformasi secara seimbang, antara ekonomi, sosial dan lingkungan, kekuatan faktor itu akan membentuk kemandirian masyarakat, disamping faktor lainnya. Secara normatif penyelenggaraan program CSR, didorong oleh kesadaran untuk bertanggung jawab secara sosial, tetapi umumnya kepentingan untuk membentuk corporate image melalui bantuan terasa lebih menonjol, sehingga belum memikirkan aspek keberlanjutan pembangunan. Keywords: CSR Islamic  Bank, Economy, Social, Environment